Evaluation of the expression of genes associated with iron metabolism in peripheral blood mononuclear cells from Type 2 diabetes mellitus patients - Hazarika, Ankita; Nongkhlaw, Bajanai; Mukhopadhyay, Arpita (Free radical biology & medicine, 2024)
Type 2 Diabetes (T2DM) has been linked to ferroptosis. This study aimed to assess expression levels of genes linked with iron metabolism in peripheral blood mononuclear cells (PBMCs) from T2DM patients and to investigate the association of these expression levels with anthropometric and clinical parameters. Gene expression of iron metabolism genes (Ferritin Light Chain, FTL; Ferritin Heavy Chain, FTH1; Transferrin Receptor, TFRC; Divalent Metal Transporter 1, SLC11A2; Ferroportin, SLC40A1) in archival PBMCs was assessed using quantitative real-time PCR assays. Correlations of gene expression with anthropometric/biochemical patient data were evaluated. The study included 36 (18 male/18 female) T2DM patients and 45 (28 male/17 female) normoglycemic (NGT) subjects with a mean age of 38.1 ± 6.8 years and 47.6 ± 8.6 years respectively. Relative expression of FTL was significantly lower in T2DM females compared to that in NGT females (P = 0.027). Relative expression of SLC40A1 was significantly lower in the T2DM group (P = 0.043) and in the T2DM females (P = 0.021). Relative expression of SLC11A2 was negatively correlated with systolic blood pressure in T2DM male patients. Relative expression of SLC40A1 was negatively associated with serum phosphorous and positively associated with serum thyroid stimulating hormone in male T2DM patients. Our findings indicate a reduction in the expression of FTL in perimenopausal T2DM females. Also, in male T2DM patients and NGT subjects, biochemical markers are significantly correlated with the expression of FTL, FTH1, SLC11A2, and SLC40A1 in PBMCs. [Display omitted]